New Impella Cardiac Power Device Used in Patient with Cardiogenic Shock due to Nonischemic Cardiomyopathy - Cena, Marek; Karam, Frances; Ramineni, Rajesh; Khalife, Wissam; Barbagelata, Alejandro (International Journal of Angiology, 2016)
The new percutaneous Impella CP (Cardiac Power; Abiomed, Inc., Danvers, MA) was designed to provide a higher level of support than Impella 2.5 (Abiomed, Inc.). We present the first documented case of a patient that was transitioned from the Impella 2.5 to Impella CP. A 48-year-old male patient with no medical history was transferred to our institution with a one day history of worsening shortness of breath. The patient was unstable and found to have monomorphic ventricular tachycardia at 220 beats/min that was cardioverted to normal sinus rhythm. An emergent right and left heart catheterization was performed showing nonobstructive coronary artery disease, biventricular failure with a left ventricular ejection fraction (LVEF) of 5 to 10%, high pulmonary capillary wedge pressure (PCWP) 22 mm Hg, right atrial (RA) pressure 22 mm Hg, and a very low cardiac index of 1.0 L/min/m2. Because of severe cardiogenic shock, Impella 2.5 was inserted providing flow up to 2.1 L/min; however, the patient remained unstable and critically ill with severe multiorgan failure. To provide better mechanical support, the device was upgraded to the new Impella CP that can provide up to 3.5 L/min of cardiac output. Over the course of the next 72 hours, the patient showed significant improvement in hemodynamics and cardiac function (LVEF 45%), with recovery of liver function. The Impella CP was removed with no complications. The new Impella CP was shown to be safe and effective for prolonged use in critically ill patients and may significantly improve their prognosis.
Keywords: cardiogenic shock; Impella CP; nonischemic cardiomyopathy